Fair Resource Allocation for Multiple Types of Services in Femto-Macro Heterogeneous Network - Chengyi Liu; Song Xing; Jing Hu; Weiwei Xia (Dianxin kexue)
The problem how to allocate the femtocell base station（FBS）resource fairly among multiple services （constant-rate services and variable-rate services）in femtocell network was focused on. Using the proportional fair to allocate the FBS transmit power for different variable-rate users was proposed to achieve fair allocated transmit rates in femto-macro heterogeneous network.The dual decomposition method was employed to find the optimal solution.Finally, the simulation results show that, besides protecting the individual QoS for each user, the proposed algorithm can not only provide fair resource allocation among variable-rate users,but also restrict the cross-tier interference to the MU.